Medical Students’ Time Management Capabilities - Mohi Ud Din, Tanzila Ishaq, Bushra Ameer Saeed Awan, Laraib Khan, Ayesha Munassr, Maria Ijaz (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Time management skills increase satisfaction and balance between work and life. Additionally, managing time effectively reduces anxiety while also making achieving goals easier. Aim: The objectives of the study were to figure out the time management skills of medical students and their relationship with socio-demographic characteristics. Methodology: This cross-sectional study was conducted in a medical college of Faisalabad.Study duration was 4 months (October 2021 to January 2022). A total of 250 students were enrolled in a study. The inclusion criteria included medical undergraduate students.A total of 50 students were enrolled from each class of MBBS through non-probability convenient sampling technique.A questionnaire titled “Time Management Assessment Questionnaire” containing 25 items developed by Wayne State University was used. A participant who had a score <29 was deemed to have poor time management abilities. A participant had average time management abilities if their overall score ranged from 30 to 44, and they had exceptional time management skills if their overall score ranged from 45 to 50. The IBM SPSS Statistics Version 25 was used for data analysis. Results: Most of the students were found to have inadequate time management skills. Class 2nd and 1st year MBBS students were found to have more inadequate time management skills followed by 4th, 3rd and final year students. Fairly well time management skills were shown by 1/3rd of participants and excellent time management skills were shown by less than 10% of participants. Conclusion: Over half percentage of medical students have poor time management abilities. Based on their socio-demographic characteristics, there are no differences in time management abilities among participants. Reading books and other publications on the subject, as well as attending related workshops and seminars, can help students improve their time management abilities. Keywords: Capabilities, medical, management, students, time, community